The Effect of a Riga Plate On Casson Hybrid Nanofluid Flow Along a Stretching Cylinder with an Exponential Heat Source and Thermal Radiation - Okuma, Silas; Adekunle , Aworinde; Adeisa Olusegun , Areo; Mariam Ololade , Akande; Peter , Adegbite; Akintayo Oladimeji , Akindele (Journal of Science and Technology, 2024)
This study investigates the effect of a Riga plate on the flow characteristics of a Casson hybrid nanofluid through a stretching cylinder embedded in a porous medium in the presence of an exponential heat source and thermal radiation. This model is used to explore the potential applications of this analysis in the fields of cancer treatment and wound healing. The governing partial differential equations are converted into a system of nonlinear ordinary differential equations using suitable similarity transformations. The governing partial differential equations (PDEs) were reduced to ordinary differential equations (ODEs) using similarity variables, and the heat transfer phenomena, fluid flow dynamics, and nanoparticle behavior in the base fluid were captured through numerical analysis. The Casson fluid model was used to capture the non-Newtonian characteristics of blood-like fluids in the circulatory system, and stretching was employed to mimic the blood vessel. The modeling involved incorporating thermal radiation (Ra) and an exponential heat source, which are encountered in cancer treatment. The Runge-Kutta order 4 with shooting technique was used to obtain numerical solutions of the governing equations, and the effects of the Casson fluid parameter, curvature parameter, nanoparticle volume fraction, Eckert number, and radiation parameter were analyzed. The results showed that the Riga plate affected the flow patterns by increasing the temperature, and the temperature distribution was improved by increasing the radiation parameter and nanoparticle concentration. The insights from this study could be used to optimize heat-based treatments for cancer and wound healing, where control of fluid dynamics and heat transfer processes is critical.